A MODEL FOR DRIVING BUDDHIST SCHOOLS TOWARD SUCCESS NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 4 - Sakkarinphanitchakul, Siranee (Journal of MCU Nakhondhat, 2022)
The Objectives of this research article were: 1) to investigate the current conditions and problems with driving Buddhist schools; 2) to develop a model for driving Buddhist schools toward success; and 3) to examine the propriety and feasibility of a model for diving Buddhist schools toward success Nakhon Si Thammarat Primary Educational Service Area Office 4. The study employed a mixed-method research. A sample group used for studying the current conditions and problems consisted of forty-five key informants who were from five Buddhist schools. Nine key informants from each school were chosen by way of purposive sampling. The data were collected via observation and interview. Descriptive statistics and percentages were used to examine the collected data. A focus group discussion with nine experts was also held to critically evaluate the propriety and feasibility of a model. The obtained data were analyzed by mean and standard deviation. From the study, the following results are found: 1) From investigating the current conditions and problems with driving Buddhist schools, it is found that schools aim at driving Buddhist schools via the use of Buddhist teachings and are founded on Buddhist school identity. Schools have kept their physical Buddhistness in active while developing continuously via a range of initiatives to foster sīla (morality), smādhi (concentration), and paññā (wisdom) in collaboration with the village, temples, and schools. The problems found were that most students still have not taken the Dhamma examination due to the Covid-19 situation. 2) From developing a model for driving Buddhist schools toward success, it is discovered that there are four stages based on Iddhipāda (the Four Paths of Accomplishment) which are: 2.1) Preparation based on Chanda (desire); 2.2) Operation based on Viriya (effort); 2.3) Evaluation based on Citta (thoughtfulness); and 2.4) Improvement and continual development based on Vīmaṃsā (Investigation). Trisikkhā (the Threefold Learning) is used in collaboration with villages, temples, and schools as well. And 3) After nine experts examined the propriety and feasibility of a model, the results showed the overall picture at the highest level ( = 4.61, S.D. = 0.49)